2019
DOI: 10.1371/journal.pone.0211784
|View full text |Cite
|
Sign up to set email alerts
|

Six-month follow up of a randomized clinical trial-phase I study in Indonesian adults and children: Safety and immunogenicity of Salmonella typhi polysaccharide-diphtheria toxoid (Vi-DT) conjugate vaccine

Abstract: Introduction There is a high global incidence of typhoid fever, with an annual mortality rate of 200,000 deaths. Typhoid fever also affects younger children, particularly in resource-limited settings in endemic countries. Typhoid vaccination is an important prevention tool against typhoid fever. However, the available polysaccharide typhoid vaccines are not recommended for children under 2 years of age. A new typhoid conjugate Vi-diphtheria toxoid (Vi-DT) vaccine has been developed for infant immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 28 publications
3
17
0
2
Order By: Relevance
“…Several studies reported the safety and immunogenicity of Vi-DT and other typhoid conjugate vaccines (TCV) among participants older than two years [ 27 , 35 , 39 , 40 , 41 ]. However, there are no data on the safety and immunogenicity of Vi-DT in children younger than two years, except for the recently published study of Vi-DT from Indonesia [ 39 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies reported the safety and immunogenicity of Vi-DT and other typhoid conjugate vaccines (TCV) among participants older than two years [ 27 , 35 , 39 , 40 , 41 ]. However, there are no data on the safety and immunogenicity of Vi-DT in children younger than two years, except for the recently published study of Vi-DT from Indonesia [ 39 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Improving the immunogenicity of typhoid conjugate vaccines in children under 2 years of age is an important advance given the significant burden of disease in young children and infants [ 5 , 7 , 33 ]. A first-in-human phase I trial conducted in the Philippines and another phase I trial conducted in Indonesia assessed the safety of Vi-DT conjugate vaccine compared to Vi polysaccharide (Typhim Vi®, Sanofi Pasteur) typhoid vaccine among healthy 2-45 years old adults and children [ 34 , 35 ]. No serious adverse events were reported in either group, and there was no difference in the frequency of solicited and unsolicited adverse events and medically significant events.…”
Section: Introductionmentioning
confidence: 99%
“…PT Bio Farma has also completed a Phase I study in Jakarta, Indonesia. PT Bio Farma’s Vi-DT vaccine was also safe and immunogenic in participants >2 years of age [ 52 ]. A Phase II study is ongoing, including children 6–23 months of age [ 53 ].…”
Section: Typhoid Conjugate Vaccinesmentioning
confidence: 99%
“…Typhoid fever remains a global public health problem in the developing world, with an estimated 14.3 million cases and 116,815 deaths each year. 5,6 Typhoid is caused by infection with S. enterica serovar Typhi, a human-restricted pathogen that enters via the gastrointestinal tract and crosses the intestinal mucosal border before disseminating in the blood and reticuloendothelial system. 7 The appearance of S. Typhi that are multiply resistant to commonly used antibiotics has restricted the ability to treat patients with typhoid fever with previously used therapies, now requiring treatment with later-generation antibiotics not always available or affordable in resource-limited settings.…”
Section: Introductionmentioning
confidence: 99%
“…Newer versions of the Vi vaccine have been developed that have conjugated the Vi polysaccharide to protein carriers, such as diphtheria toxoid (DT), and the physical, chemical, and immunologic properties of Vi-DT conjugate have been well characterized. 11 Recent studies suggest that conjugation of Vi to DT improves immunogenicity, especially in young children, 5,12 and results in more prolonged immune responses and longer term protection following parenteral vaccination through the induction of T-cell-dependent memory B-cell responses to the Vi polysaccharide. 5,12 In this study, we evaluated systemic, mucosal, and memory B-cell immune responses to Vi and Vi-DT conjugate vaccines when administered transcutaneously in a mouse model, with and without cholera toxin (CT) given at the same transcutaneous site as an adjuvant.…”
Section: Introductionmentioning
confidence: 99%